Glucocorticoids Are Not Associated with Bone Mineral Density in Patients with Polymyalgia Rheumatica, Giant Cell Arteritis and Other Vasculitides—Cross-Sectional Baseline Analysis of the Prospective Rh-GIOP Cohort - Andriko Palmowski; Edgar Wiebe; Burkhard Muche; Sandra Hermann; Christian Dejaco; Eric L. Matteson; Frank Buttgereit (Cells, 2022)
Background: Glucocorticoids (GCs) can cause osteoporosis (OP). Prior observational research on bone density and the effects of GCs in polymyalgia rheumatica (PMR) and vasculitides is scarce and inconclusive. Methods: Rh-GIOP is a prospective cohort study of bone health in patients with inflammatory rheumatic diseases. In this cross-sectional baseline analysis, we focused on patients with PMR and different forms of vasculitides. Multivariable linear regression was used to model the effect of current and cumulative GC intake on the minimum T-score at any site (mTs; at either lumbar spine or hip), with comprehensive adjustment for confounders. In separate models, GCs were modelled both as continuous and categorical predictors. Sensitivity analyses, stratifying by measurement site and disease, were conducted. Results: A total of 198 patients, with a mean age of 67.7 ± 11.4 years and a mean disease duration of 5.3 ± 6.3 years, were included. Most patients suffered from PMR (36%), giant cell arteritis (26%) or granulomatosis with polyangiitis (17%). Women comprised 66.7% of the patients, and 87.4% were currently taking GCs. The mean CRP was 13.2 ± 26.1 mg/L. OP diagnosed by dual energy X-ray absorptiometry (DXA) (T-score ≤ −2.5) was present in 19.7% of the patients. While 88% were taking vitamin D supplements, calcium supplementation (4%) and treatment with anti-resorptive agents (17%) were relatively infrequent. Only 7% had a vitamin D deficit. Neither current (β(continuous model) = −0.01, 97.5% CI –0.02 to 0.01; p(all models) ≥ 0.49) nor cumulative (β(continuous model) = 0.01, 97.5% CI −0.04 to 0.07; p(all models) ≥ 0.35) GC doses were associated with mTs in any model. CRP was not associated with mTs in any model (p(all models) ≥ 0.56), and no interaction between CRP and GC intake was observed (p for interaction(all models) ≥ 0.32). Across all analyses, lower body mass index (p(all models) ≤ 0.01), history of vertebral fractures (p(all models) ≤ 0.02) and proton-pump inhibitor intake (p(all models) ≤ 0.04) were associated with bone loss. Sensitivity analyses with femoral neck and lumbar spine T-scores as dependent variables led to similar results as the analysis that excluded patients with PMR. Conclusions: In this cohort of PMR and vasculitides, we found a similar prevalence of OP by DXA to the overall elderly German population. Vitamin D supplementation was very common, and vitamin D insufficiency was less frequent than expected in Germans. There was no association between current or cumulative GC intake, CRP and impaired bone density. Proton-pump inhibitors seem to be a major, but somewhat neglected, risk factor for OP and should be given more attention. Our findings require confirmation from longitudinal analyses of the Rh-GIOP and other cohorts.